2015
DOI: 10.3109/10826084.2015.1027923
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Proposed Changes for the DSM-5 on Diagnoses of First-time DUI/DWI Offenders

Abstract: Driving while impaired (DWI) is a frequently committed crime with enormous individual and social costs. The type of disposition and/or treatment appropriate for an individual offender is often determined, in part, by diagnostic criteria based on the American Psychiatric Association's Diagnostic and Statistics Manual. The DSM-5 significantly modified these criteria by eliminating legal problems as a criterion and dropping the categories of abuse and dependence. A brief substance abuse focused interview was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The treatment of AUD among people in the justice system is especially important to consider with the removal of legal problems as one of the criteria used to diagnose disordered substance use in DSM-5. For instance, one study found that people with initial DWI offenses met criteria for substance abuse using DSM-IV-TR criteria but were no longer diagnosed with an AUD using DSM-5 criteria (Baley & Hoffman, 2015). Despite research consistently showing that AUD is highly prevalent among people involved in the criminal justice system, people arrested for DWI are often incarcerated for brief periods and/or referred to educational classes rather than substance use treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of AUD among people in the justice system is especially important to consider with the removal of legal problems as one of the criteria used to diagnose disordered substance use in DSM-5. For instance, one study found that people with initial DWI offenses met criteria for substance abuse using DSM-IV-TR criteria but were no longer diagnosed with an AUD using DSM-5 criteria (Baley & Hoffman, 2015). Despite research consistently showing that AUD is highly prevalent among people involved in the criminal justice system, people arrested for DWI are often incarcerated for brief periods and/or referred to educational classes rather than substance use treatment.…”
Section: Discussionmentioning
confidence: 99%
“…One concern is that DSM-5 AUD classification might miss young people in high-risk groups, such as repeat DUI offenders, that DSM-IV alcohol abuse would have captured, which may result in fewer people receiving any attention or care for their recidivism. Targeted educational programs or other community prevention programs may not suffice for this group of recidivists [57]. While DOs would need early detection and management, population-based and evidence-informed public health prevention measures and adequately enforced legislations such as tighter drink-driving regulations remain key for preventing DUI [58,59], and reducing the risk of "over-pathologizing" human behaviors [60].…”
Section: Plos Onementioning
confidence: 99%
“…A study of first-time driving under the influence (DUI)/driving while intoxicated (DWI) offenders found that a significant portion of these cases acknowledged only driving under the influence (reflective of the DSM-IV criterion related to use in dangerous situations) and the legal problem of being arrested [22]. With the DSM-IV, these cases would have received an abuse diagnosis, but will not receive a diagnosis with the DSM-5.…”
Section: Implications For Treatment Under the Dsm-5mentioning
confidence: 99%